Biocompatibility of submicron Bioglass® powders obtained by a top‐down approach. Issue 5 (30th November 2013) - Dörfler, Anja; Detsch, Rainer; Romeis, Stefan; Schmidt, Jochen; Eisermann, Claudia; Peukert, Wolfgang; Boccaccini, Aldo R.
Abstract In this study in vitro bioactivity and biocompatibility of two submicron 45S5 Bioglass® powders obtained by top‐down processing have been evaluated and are compared to the as‐received powder. Both submicron powders exhibited flake‐like morphologies with lateral extensions of only a few microns; the flake thickness accounted for a few tens of nanometers. Enhanced in vitro bioactivity was found for the comminuted powders upon immersion in simulated body fluid. In vitro biocompatibility was evaluated by incubation of MG‐63 osteoblast‐like cells with various amounts (0–200 µg/mL) of the glass powders. Neither LDH‐activity nor mitochondrial activity (WST‐8) tests indicated cell toxicity. Increased mitochondrial activity was found for the submicron powders: incubation with high amounts revealed up to a threefold increase of osteoblast activity (ALP‐activity). An overgrowth of the formed mineralized phase with phenotypical MG‐63 cells was found by staining only for the submicron glasses. A distance ring is formed for the as‐received powder. Superior bioactivity markers are found for shorter process times, that is, lower mass specific surface areas. This is attributed to the formation of carbonates during the comminution process. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 952–961, 2014.